Probabilistic Analysis Approach of Uncertainties in Fatigue Life Simulations of an Oil Tanker Vessel - Ozguc, Ozgur (Transactions on Maritime Science, 2022)
Fatigue damage is known to occur more commonly in certain ship types and hull construction element categories. The significance of prospective fatigue damage is proportional to the number of potential damage points of the investigated type for the ship structure in question, as well as the consequences of such damage. The present study introduces an overview of different fatigue analysis methods and provides advice on the accuracy of different methods for different locations on a vessel and a ranking of the methods. A probabilistic analysis of hopper knuckle fatigue analysis is supported by example uncertainty calculations, using four different fatigue methods for the hopper knuckle of an oil tanker vessel. The calculation of bias and uncertainty is supported by creating input to PROBAN tool, where the uncertainty calculations are being performed. The calculations show that the resulting fatigue damage distributions vary significantly. The median (50%) varies between 0.7 and 1.1 for the four methods, where 1.0 is the assumed correct damage for the calculations. The most probable damage varies between 0.4 and 0.9 for the four methods.